Technology transfer University-SMES as a link option - Trasviña Soto, Irma Cecilia (Universidad de Sonora, 2017)
The present research aims to propose a model of technology transfer University-SMEs as a linking option. It is a mixed, non-experimental and cross- sectional study, in order to describe the constructs and variables related to relevant aspects to achieve University-SME technology transfer. In order to respond to the objective formulated a statistical instrument was designed, which in turn was validated by expert opinion through the Delphi method, leaving a definitive questionnaire that was applied in 71 SME entrepreneurs. Multivariate analysis of multiple linear regression was used for the statistical analysis of the obtained information. The results of the present investigation have a series of business, governmental and social implications that, when developing in an integral way, could contribute to the birth of strategies that will solve the problem under study. SMEs, for the most part, are not able to survive in isolation in today's changing and competitive market, which is why they decide to enter into strategic alliances with other business organizations with related and unrelated businesses. In recent times, diverse experiences and initiatives have been appearing in the international context that promote the establishment of cooperation agreements between institutions, as well as the development of technological parks.